Cerium oxide nanoparticles loaded nanofibrous membranes promote bone regeneration for periodontal tissue engineering - Ren, Shuangshuang; Zhou, Yi; Zheng, Kai; Xu, Xuanwen; Yang, Jie; Wang, Xiaoyu; Miao, Leiying; Wei, Hui; Xu, Yan (Bioactive Materials, 2021)
Bone regeneration is a crucial part in the treatment of periodontal tissue regeneration, in which new attempts come out along with the development of nanomaterials. Herein, the effect of cerium oxide nanoparticles (CeO2 NPs) on the cell behavior and function of human periodontal ligament stem cells (hPDLSCs) was investigated. Results of CCK-8 and cell cycle tests demonstrated that CeO2 NPs not only had good biocompatibility, but also promoted cell proliferation. Furthermore, the levels of alkaline phosphatase activity, mineralized nodule formation and expressions of osteogenic genes and proteins demonstrated CeO2 NPs could promote osteogenesis differentiation of hPDLSCs. Then we chose electrospinning to fabricate fibrous membranes containing CeO2 NPs. We showed that the composite membranes improved mechanical properties as well as realized release of CeO2 NPs. We then applied the composite membranes to in vivo study in rat cranial defect models. Micro-CT and histopathological evaluations revealed that nanofibrous membranes with CeO2 NPs further accelerated new bone formation. Those exciting results demonstrated that CeO2 NPs and porous membrane contributed to osteogenic ability, and CeO2 NPs contained electrospun membrane may be a promising candidate material for periodontal bone regeneration.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Bone regeneration; CeO; Electrospinning; Fibrous membrane; Periodontal ligament stem cells